2022
DOI: 10.3390/vaccines10030476
|View full text |Cite
|
Sign up to set email alerts
|

Does Hospitalization Change the Perception of COVID-19 Vaccines among Unvaccinated Patients?

Abstract: The COVID-19 vaccination has been the subject of unprecedented misinformation, false news, and public concerns. This study presents a unique analysis comprising persons who were not vaccinated and became ill. It investigates reasons for not vaccinating and evaluates how the personal experience of COVID-19 affected further attitudes and decisions related to health. The study included 730 consecutive unvaccinated patients hospitalized in 12 centers in Poland during the autumn 2021 pandemic wave. The most frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…Those who declared no interest reported a high number of adverse events and their increased nuisance level after receiving the third dose. This highlights that past experiences play a role in vaccine perception and shape future decisions regarding vaccination, as already documented in previous research [ 22 , 49 ].…”
Section: Discussionsupporting
confidence: 71%
“…Those who declared no interest reported a high number of adverse events and their increased nuisance level after receiving the third dose. This highlights that past experiences play a role in vaccine perception and shape future decisions regarding vaccination, as already documented in previous research [ 22 , 49 ].…”
Section: Discussionsupporting
confidence: 71%
“…This is because the COVID-19 pandemic has seen an unprecedented flood of misinformation spread worldwide and a rise of various conspiracy theories that undermined the trust in health authorities [ 26 , 215 , 216 ]. In the case of some individuals, a belief in conspiracy theories can be emotionally rooted to the point that even personal experiences with COVID-19 are insufficient to change one’s perception [ 217 ].…”
Section: Challenges Of Oral Antiviral Treatment Of Covid-19mentioning
confidence: 99%
“…The results of the study are in compliance with the results of another study carried out also on Polish population but among unvaccinated patients hospitalized due to COVID-19. It demonstrated that one of the most frequent reasons behind the refusal to receive the vaccine were concerns over the adverse effects and disbelief that the vaccines were sufficiently tested [ 47 ], despite the abundant and still increasing knowledge on COVID-19 vaccines and their effects [ 48 ]. It is worth stressing, however, that the other most significant reason declared as discouraging people from vaccination was the conviction that the person will not be affected by COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth stressing, however, that the other most significant reason declared as discouraging people from vaccination was the conviction that the person will not be affected by COVID-19. After succumbing to severe COVID-19, only approximately one-third of them still expressed vaccine hesitancy while the rest of the patients regretted their decision not to receive the vaccine and declared their will to receive it after discharge [ 47 ].…”
Section: Discussionmentioning
confidence: 99%